Enhanced Virgin Coconut Oil (EVCO) as Natural Postmilking Teat Germicide to Control Environmental Mastitis Pathogens - Peng, Koh Soo; Harun, Dahlia; Amin, Maswati Mat; Long, Kamariah (International Journal of Biotechnology for Wellness Industries, 2016)
The antimicrobial capability of oil containing medium-chain fatty acids and their corresponding monoglycerides, known as Enhanced Virgin Coconut Oil (EVCO) against microorganisms isolated from bovine mastitis milk was studied. EVCO contains an effective amount of medium-chain free fatty acids (caprylic, capric and lauric acid) and their corresponding derivatives (monocaprylin, monocaprin and monolaurin) can act as antimicrobial agent with broad spectrum of antimicrobial properties. An in vitro assessment of EVCO against bovine mastitis microorganisms isolated from locally collected mastitis milk samples was conducted to determine its minimum bactericidal concentration (MBC>99). In general, EVCO exhibited its great antimicrobial capability to kill all mastitis microorganisms isolated from the mastitis milk sample at different concentrations of MBC>99 value. In fact, EVCO was found more effective to kill Mycoplasma sp. and gram positive microbes rather than gram negative microbes, especially in Mycoplasma bovis, Acholeplasma oculi, Enterococcus sp., Streptococcus sp. and Staphylococcus aureus with lower MBC>99 values in comparison with the synthetic antibiotic, Mastivet. A further investigation of the antimicrobial activities of EVCO against Staphylococcus aureus and Mycoplasma bovis against time revealed that EVCO was more efficient in killing these two microorganisms in a shorter time at a lower concentration as opposed to Mastivet. These findings indicated that EVCO has great potential application in postmilking teat germicide, which can be used as a preventive measure to control mastitis cases, especially against environmental mastitis pathogens.